Lymphocyte neutrophilic index in the prediction of type 4 myocardial infarction - Rodriguez Blanco, Suilbert; Véliz Martínez, Pedro Luis; Tamargo Barbeito, Teddy Osmín; Pérez Yanez, Lázara Mirta (Revista Cubana de Medicina, 2021)
Introduction: Type 4a myocardial infarction is a complication of percutaneous coronary intervention, which is associated with an inflammatory process. The lymphocyte neutrophilic index, as a marker of inflammation, could be included in your risk stratification. Objectives: To assess the sensitivity, specificity, predictive values and the variation of the lymphocyte neutrophilic index in the prediction of type 4a myocardial infarction. Methods: A prospective cohort investigation was carried in 184 patients who underwent percutaneous coronary intervention. Results: For a value higher than and equal to 2.74, the index showed 72.0%, sensitivity, 74.8% specificity and 94.4% negative predictive value in the prediction of type 4a infarction. The variation of the index was an independent predictor of the complication p <0.001. Conclusions: The lymphocyte neutrophil index has high sensitivity, specificity and negative predictive value in the prediction of type 4a infarction. Its elevation six hours after the procedure is an independent predictor for this complication. Keywords: lymphocyte neutrophilic index; type 4a heart attack; prediction.